Dinamika Environmental Kuznets Curve dan Urbanisasi - Ade Yunita Mafruhat; Rival Padillah (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. This study examines the applicability of the Environmental Kuznets Curve (EKC) and the role of urbanisation in environmental degradation in Brunei Darussalam during the period 1974–2022, using PM2.5 emissions as an indicator of air quality. This study departs from the condition of Brunei as a high-income oil-based country with a high level of urbanisation, but without any indication of a decline in emissions as predicted by the EKC. This study aims to examine the relationship between GDP per capita, urbanisation, and PM2.5 emissions and to analyse their long-term and short-term dynamics. The method used is a quantitative approach with time series econometrics. Annual secondary data included GDP per capita, urbanisation rates, and PM2.5 emissions. All variables were transformed into natural logarithms and analysed using Autoregressive Distributed Lag (ARDL) and Error Correction Model (ECM) models, accompanied by stationarity, cointegration, and diagnostic tests. The results show that the EKC is not evident in Brunei, while urbanisation has a significant positive effect on PM2.5 emissions with a relatively high long-term adjustment speed. This study concludes that reducing environmental degradation in Brunei cannot rely solely on economic growth but requires urbanisation management policies and energy mix reforms. Abstrak. Penelitian ini mengkaji keberlakuan Environmental Kuznets Curve (EKC) serta peran urbanisasi terhadap degradasi lingkungan di Brunei Darussalam periode 1974–2022 dengan menggunakan emisi PM2,5 sebagai indikator kualitas udara. Studi ini berangkat dari kondisi Brunei sebagai negara berpendapatan tinggi berbasis migas dengan tingkat urbanisasi yang tinggi, namun tanpa indikasi penurunan emisi sebagaimana diprediksi oleh EKC. Penelitian ini bertujuan menguji hubungan antara PDB per kapita, urbanisasi, dan emisi PM2,5 serta menganalisis dinamika jangka panjang dan jangka pendeknya. Metode yang digunakan adalah pendekatan kuantitatif dengan ekonometrika time series. Data sekunder tahunan meliputi PDB per kapita, tingkat urbanisasi, dan emisi PM2,5. Seluruh variabel ditransformasi ke dalam logaritma natural dan dianalisis menggunakan model Autoregressive Distributed Lag (ARDL) dan Error Correction Model (ECM), disertai uji stasioneritas, kointegrasi, dan diagnostik. Hasil penelitian menunjukkan EKC tidak terbukti di Brunei, sementara urbanisasi berpengaruh positif signifikan terhadap emisi PM2,5 dengan kecepatan penyesuaian jangka panjang yang relatif tinggi. Penelitian ini menyimpulkan bahwa penurunan degradasi lingkungan di Brunei tidak dapat hanya mengandalkan pertumbuhan ekonomi, tetapi memerlukan kebijakan pengelolaan urbanisasi dan reformasi bauran energi.